INFRASTRUCTURE APPROACH AS INNOVATION METHOD OF TERRITORY DEVELOPMENT OF RUSSIA FEDERATION - F. Sharipov; O. Timofeev (Вестник университета, 2016)
The article reviews the examples of an industrial infrastructure development in the Russian Federation and the examples of an international cooperation in this field. It is particularly important that the crucial today’s perspectives of the Russian Federation and the People’s Republic of China cooperation in the Chinese project of the Silk way Economic belt with the Russian Eurasian initiatives integration have been reviewed in the article. The result of the article is the generalization of the latest trends in the attraction of foreign investments to the implementation of the most important infrastructure projects in the territory. It can be used in the developing or the improvement of the regional industrial infrastructure development programs by the industry and the international economic, innovative, educational activities interaction.